Spiritism as a target of 'annihilation': conceptual clarification and exemplification of a rhetorical strategy - Usarski, Frank (Social compass, 2019)
The rhetorical strategy of annihilation appears in situations of conflict between different world-views. It is the attempt of one of the parties involved to attribute an inferior status to the adversary. The technique requires the capacity of a social actor of influencing the public image of the phenomenon in question in a way that a public interest in the campaign becomes obvious. The success of this process of social construction depends on a twofold rhetorical talent of the 'constructor'. The first faculty is to reduce the complexity of the challenging phenomenon to alleged 'core elements'. The second one is to associate these 'core elements' to pre-established negative definitions so that the 'enemy' appears as a mere variant of a well-known unacceptable social phenomenon. In order to illustrate how and why the strategy of annihilation works, the article refers to the campaign against Spiritism driven by Brazilian authorities between 1890 and 1940.